Enseigner l’Amérique latine aujourd’hui - Sylvie Mégevand (Caravelle)
In the French Hispanic field, the Spanish American teaching in secondary as well as in university education is widely represented, through various specific subjects: literature, civilisation, arts... Every course presents its peculiarities as well as its epistemology concerns, aiming to underline the subcontinent’s complexity –going beyond its apparent unity– and fighting against the temptations dealing with exoticism and miserabilism.